2016
DOI: 10.1038/srep38174
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of plasma microRNAs as biomarkers for myotonic dystrophy type 1

Abstract: Non-invasive and simple to measure biomarkers are still an unmet need for myotonic dystrophy type 1 (DM1). Indeed, muscle biopsies can be extremely informative, but their invasive nature limits their application. Extracellular microRNAs are emerging humoral biomarkers and preliminary studies identified a group of miRNAs that are deregulated in the plasma or serum of small groups of DM1 patients. Here we adopted very stringent selection and normalization criteria to validate or disprove these miRNAs in 103 DM1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 37 publications
1
54
0
2
Order By: Relevance
“…Several reports have demonstrated that miRNAs are potential biomarkers of different diseases, such as cancer, liver injury, or heart failure . The expression profile of miRNAs has also been studied in different muscle diseases such as DMD, myotonic dystrophy, and FSHD . In these studies, several miRNAs have a different pattern of expression when compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have demonstrated that miRNAs are potential biomarkers of different diseases, such as cancer, liver injury, or heart failure . The expression profile of miRNAs has also been studied in different muscle diseases such as DMD, myotonic dystrophy, and FSHD . In these studies, several miRNAs have a different pattern of expression when compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to MCS caused skeletal muscle atrophy also in a mouse model of COPD 43 and upregulated several pathways of metabolic processes and tissue degradation in muscles 56 . Evaluation of circulating miRNAs in myotonic dystrophy patients suggested that miRNAs might be useful as humoral biomarkers of that muscle disease 57 . The poor correlation between early alterations of miRNA profiles in the lung and in the blood serum of MCS-exposed mice is in agreement with the results of a previous study in mice exposed to the same agent during the first 4 months of life and thereafter kept in filtered air for an additional 3.5 months, when smoking-related lung tumors were detectable 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on mouse and rat models have also proved its involvement in spermatogenesis (Luo et al, 2015 ) and testis differentiation (Rakoczy et al, 2013 ), chondrogenesis and growth (Pando et al, 2012 ; Waki et al, 2016 ), and sensitivity of fetal neural development to ethanol and nicotine (Balaraman et al, 2012 ). Circulating miR-140-3p has been identified as dysregulated in either plasma or serum from patients with different pathological conditions and it has already been suggested as a potential biomarker for some of them, like myotonic dystrophy type 1 and type 2 (Perfetti et al, 2014 , 2016 ), biliary atresia (Peng X. et al, 2016 ), papillary thyroid carcinoma (Li et al, 2015 ), wet age-related macular degeneration (Ertekin et al, 2014 ), and myasthenia gravis (Nogales-Gadea et al, 2014 ). Its potential as non-invasive intracellular biomarker has also been demonstrated on blood samples from patients affected by coronary artery disease (Taurino et al, 2010 ; Karakas et al, 2017 ) and type 2 diabetes mellitus, (Collares et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%